2020
DOI: 10.1002/jcb.29670
|View full text |Cite
|
Sign up to set email alerts
|

NCALD affects drug resistance and prognosis by acting as a ceRNA of CX3CL1 in ovarian cancer

Abstract: Drug resistance, an impenetrable barrier in the treatment of ovarian cancer (OC), is often associated with poor outcomes. Hence, it is urgent to discover new factors controlling drug resistance and survival. The association between neurocalcin delta (NCALD) and cancer drug resistance is poorly understood. Here, we reveal that NCALD messenger RNA expression, probably regulated by DNA methylation and microRNAs, was significantly downregulated in at least three independent microarrays covering 633 ovarian carcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 49 publications
1
18
0
Order By: Relevance
“…Overexpressing miR-181d inhibits metastasis of CRC cells through PEAK1 (57). In addition, previous studies have shown that NCALD may regulate chemo-resistance by the ERK1/2, NF-κB and immune response pathways (58) and prognosis via CX3CL1 in ovarian cancer (59). The results of the present study demonstrated that exosomal miR-181d-5p binds directly with NCALD to regulate 5-FU sensitivity.…”
Section: Discussionsupporting
confidence: 68%
“…Overexpressing miR-181d inhibits metastasis of CRC cells through PEAK1 (57). In addition, previous studies have shown that NCALD may regulate chemo-resistance by the ERK1/2, NF-κB and immune response pathways (58) and prognosis via CX3CL1 in ovarian cancer (59). The results of the present study demonstrated that exosomal miR-181d-5p binds directly with NCALD to regulate 5-FU sensitivity.…”
Section: Discussionsupporting
confidence: 68%
“…TCGA data found that the expression of NCALD in platinum-resistant patients was lower than that in platinum-sensitive patients. Patients with low NCALD expression have poor overall survival (OS) and progression-free survival (PFS) [ 74 ]. Our findings are consistent with this report.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have indicated that ceRNA-related genes strongly impact cancer pathogenesis, progression and prognosis (28). Regarding OC, several studies have explored ceRNA networks in OC based on TCGA (17) and Gene Expression Omnibus (29) data and these studies predominantly focused on certain clinical traits in the OC cohort, such as recurrence (30) and drug resistance (31). However, this is far from ideal, as differential expression between OC and healthy tissues was not considered.…”
Section: Discussionmentioning
confidence: 99%